Educational intervention on high blood pressure aimed at childbearing age women from a doctor's office. Nuevitas, 2020-2023 - Mayra Pérez Basulto; Arvelio Adán Sánchez; Julio Michel Arias Manganelly; Olenis Alicia Aldana Ramos; Sheela Yalis Armenteros Salgado; Maigret Calderón Cruz (Medisur)
Foundation: high blood pressure constitutes a cardiovascular system disease, in addition to being considered a major modifiable risk factor by the World Health Organization; and a serious health problem to be solved throughout the world. Its prevention and educating about it is essential. Objective: to describe the educational intervention results to raise the knowledge level about arterial hypertension in childbearing age women. Methods: descriptive, intervention study, carried out between September 20202 and September 2023, which included 86 women of childbearing age belonging to Nuevitas’ Medical Office No. 8, Camagüey province. A questionnaire was applied to measure the knowledge level before and after the educational intervention. The analyzed variables were: presence of risk factors, triggering diseases, symptoms and signs, and measures to prevent high blood pressure. Results: high salt consumption was the predominant risk factor (55.8%). At the beginning, the knowledge level regarding diseases that can cause high blood pressure; and on symptoms and signs, it was medium and low in 88.4% of the respondents, respectively. After the intervention, all these parameters improved in correspondence with a high knowledge level in more than 80% of the cases. Conclusions: the educational intervention achieved its goal, by significantly increasing knowledge related to the prevention of high blood pressure, its symptoms and signs, as well as other important variables in the series under study.